Managerial Accounting and Society: Emerging Factors for ‘Decision Making’ of Accountants in the Modern Era - Masoom, Muhammad Rehan; Zaman, Fareen (American Journal of Trade and Policy, 2017)
The managerial accounting offers a universal set of tools to manage the administration and acts as patterned entities for producing a return for the organization. In doing so, the chief problem faced by a professional and academic discipline like accounting is that it has to deal with two distinct planes: one is the theoretical stage, and the other is on the practical height. Since the influence of accounting affects areas beyond mere corporate and business entities to the day-to-day social role of accounting, the discipline must pay proper discretion in addressing both the aspects.  This paper address three complicates issues that the modern day accounting is facing. First, it attempts to shed lights on the sociological concepts applicable in accounting to comprehend the implicative insinuations. Second, the civil discourse and the decision-making edifice of the management have taken under consideration. Third, it intends an approach to reconstruct the behavioral accounting.
Keywords: Managerial Accounting and Society; Polyphonic debate; Behavioral Implications; Public Discourse; Decision-Making; Social Accounting